C31-Selective substitution of cationic N-heteroaromatic groups into a 3-vinylated chlorophyll-a derivative. Issue 22 (14th March 2019) - Takahashi, Tatsuya; Ogasawara, Shin; Echizen, Shihoko; Shinozaki, Yoshinao; Tamiaki, Hitoshi
Abstract : A variety of N-heteroarenes were C3 1 -selectively introduced for a chlorophyll- a derivative through a C–N + bond by using iodine and a silver(i ) salt. Abstract : A variety of N-containing heteroarenes were site-selectively introduced at the C3 1 -position of a chlorophyll- a derivative possessing a 3-vinyl group through a C–N + bond via oxidative reactions using iodine in the presence of a silver(i ) salt. Electron-rich N-heteroarenes were effectively substituted, while electron-withdrawing or bulky nitrogen-neighboring substituents suppressed the reactivities. The cationic products formed were characterized by 1D/2D NMR, and their optical properties were also investigated.